Synthesis and Biological Activities of Some New Pyrimidine Derivatives - Seada, M.; Abdel-Halim, A.M.; Irbahim, S.S.; Abdel-Megid, M. (Asian Journal of Chemistry, 2010)
Synthesis of 4-chloro-5-cyano-2-methyl-6-phenylpyrimidine (Ib) and its reactions with acetamidine hydrochloride, guanidine hydrochloride, cyanoacetamide, benzilmonohydrazone, sodium azide, semicarbazide hydrochloride, acidhydrazides, active methylene compounds, aromatic amines and thiourea have been investigated. Also, the reactions of 5-cyano-2-methyl-6-phenyl-4 (3H)-pyrimidinethione (IXf) with ethyl iodide, ethyl chloroacetate, phenacyl bromide, acrylonitrile and chloroheterocycle systems were reported.